KENDALA PUBLIC SPEAKING DAN SOLUSI KECEMASAN KOMUNIKASI - Talalu, Taufik R (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2023)
This article aims to understanding on types of public speaking barrier along with solutions for communication apprehension in students of Communication and Islamic Department, IAIN Sultan Amai Gorontalo. A communication apprehension as a public speaking barrier is depicted based on the understanding of perspectives of cognitive and behavioral as well as types of communication apprehension. This research method is descriptive qualitative. The data obtained was collected from interviews and observations. The study’s findings reveal that: 1) the communication apprehension experienced by students is driven by negative thoughts and trends to avoid public speaking; 2) the types of communication apprehension experienced by students are traitlike communication apprehension, context-based communication apprehension, audience communication apprehension, and situational communication apprehension; and 3) while preparing for a certain occasion, the communication apprehension experienced by the student is coped with shifting focus, having positive self-talk, doing exercise, and not memorizing material. In addition, the students do role taking, breathing exercises, right foods eating, and body exercises before performing.